2004
DOI: 10.1007/bf02898066
|View full text |Cite
|
Sign up to set email alerts
|

Metallothioneins and brain injury: What transgenic mice tell us

Abstract: In rodents, the metallothionein (MT) family is composed of four members, MT-1 to MT-4. MT-1&2 are expressed in virtually all tissues including those of the Central Nervous System (CNS), while MT-3 (also called Growth Inhibitory Factor) and MT-4 are expressed prominently in the brain and in keratinizing epithelia, respectively. For the understanding of the physiological functions of these proteins in the brain, the use of transgenic mice has provided essential information. Results obtained in MT-1&2-null mice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 151 publications
2
7
0
Order By: Relevance
“…It has been established clearly that MT‐II administered exogenously induces neuroprotection in a number of injury models as long as the BBB is altered (Penkowa and Hidalgo, 2000, 2001; Giralt et al, 2002b; Chung et al, 2003; Xie et al, 2004). It is generally agreed that mammalian MT‐I and MT‐II will likely be functionally equivalent, and in fact results obtained in Mt1&2 KO mice are consistent with those obtained in mice overexpressing MT‐I regarding brain neurobiology (Hidalgo et al, 2001; Hidalgo, 2004). Nevertheless, direct comparative studies validating this have not been carried out.…”
Section: Discussionsupporting
confidence: 53%
“…It has been established clearly that MT‐II administered exogenously induces neuroprotection in a number of injury models as long as the BBB is altered (Penkowa and Hidalgo, 2000, 2001; Giralt et al, 2002b; Chung et al, 2003; Xie et al, 2004). It is generally agreed that mammalian MT‐I and MT‐II will likely be functionally equivalent, and in fact results obtained in Mt1&2 KO mice are consistent with those obtained in mice overexpressing MT‐I regarding brain neurobiology (Hidalgo et al, 2001; Hidalgo, 2004). Nevertheless, direct comparative studies validating this have not been carried out.…”
Section: Discussionsupporting
confidence: 53%
“…The high capacity of MT to bind both essential and nonessential metal ions in vivo and in vitro strongly suggests a role in metal ion storage, metabolism and trafficking of Cu and Zn, as well as sequestration of Cd and Hg; however, the exact function of MT remains undefined. More recently, MT has been implicated in brain tissue repair through anti-inflammatory, antioxidant and antiapoptotic roles [7][8][9][10][11], as well as in chemotherapy resistance [12]. Domain-independent but metal ion-directed folding of MT results in the formation of discrete metalthiolate clusters within each of the a and b domains with stoichiometries of [M 4 (S cys ) 11 ] and [M 3 (S cys ) 9 ], respectively, for divalent metal ions (M) [13][14][15].…”
mentioning
confidence: 99%
“…In TLE-TD group, MT-I/II expression correlated positively with neuronal population only in CA4. In the CNS, MT-I/II are expressed mainly by astrocytes [46] and, when the tissue suffers an injury, increased MT-I/II expression is observed in astrocytes and microglias [46], [32]. In our study, an increased expression of MT-I/II was observed in astrocytes and Figure 5.…”
Section: Discussionsupporting
confidence: 55%